(untitled) (Journal of National Institute of Ophthalmology, 2026)
Anisometropic amblyopia is the most common cause of visual morbidity in childhood which is characterized by reduced spatial vision due to refractive error. This study was planned to determine the visual outcome after full refractive correction of anisometropic amblyopia among 5-15 years old children. The Cross sectional interventional study was conducted conducted in the Departments of Community Ophthalmology and Ophthalmology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from March 2017 to august 2019. Children (5-15 years) having myopic, hypermetropic & astigmatic refractive error between two eyes will be minimum 1.0 D difference after refraction and didn’t get any treatment for this problem yet were the study population. Total 52 untreated children were included in the study. 3 children did not attend the follow up visit. The mean age of the subjects of our study was 9.47 years, range of age was 5-15 years. 44 (89.8%) patients were bilateral & 5 (10.2%) were unilateral. After full correction of refractive error with spectacles alone improved anisometropic amblyopic eyes visual acuity an average of 2.3 lines in snellen’s chart. Visual acuity improved from baseline by 2 or more lines (95% CI) in 85% of the patients and by 3 or more lines in 49.3%. This improvement is statistically significant (P<0.0001). Additionally, amblyopia resolved in 7 of 49 (15%) patients with residual amblyopia who continued to be treated with spectacles even after completion of follow up plan. Improvement of visual acuity continued beyond the initial 12 weeks of spectacle wearing for 37 (75.5%) of the 49 patients completing the initial 12 week visit, after completing 24 weeks, it was 26 (53.1%). The mean VA of the right eyes at baseline was 0.45 Log MAR unit. In 2nd visit shows the mean of VA is 0.34 log MAR unit and in 3rd visit mean is 0.23 log MAR unit. Total improvement in right eye was 0.22 logMAR unit. The mean VA of the left eyes at baseline was 0.51 LogMAR unit. In 2nd visit shows the mean of VA is 0.37 logMAR unit and in 3rd visit VA mean is 0.30 logMAR unit. Total improvement in right eye was 0.21 logMAR unit. Average improvement in both eyes 0.215 logMAR unit. So, results shows that refractive correction is a powerful treatment modality for young children with anisometropic amblyopia. If we can detect them earlier then we should have given these children a better vision & prosperous life. J.Natl.Inst.Ophthalmol.2024;7(2): 20-27